THE EFFECT OF SERVICE QUALITY ON PORT OPERATIONAL PERFORMANCE AND SATISFACTION: A STUDY OF TRANSPORTATION AND PASSENGER COMPANIES AT LUWUK PORT IN BANGGAI DISTRICT - Wahyu Wibowo; Edhie Budi Setiawan; Lira Agusinta; Ridho Bramulya Ikhsan (JURNAL ILMIAH EDUNOMIKA, 2024)
Understanding the behavior of freight and passenger transport companies as users of port services is essential to evaluate service quality performance because it will have an impact on port operational performance and also port service user satisfaction (companies and passengers). Therefore, this study aims to examine the impact of service quality on port operational performance and customer satisfaction from the perspective of port service users. This research uses qualitative and quantitative methods. The quantitative method uses PLS-SEM, while the qualitative method uses IPMA. Data were collected from two sample groups by distributing questionnaires to 50 freight transportation companies and 50 passengers of Luwuk Port in Banggai Regency. The results prove that service quality positively and significantly affects port operational performance and satisfaction in the sample group of freight and passenger transportation companies. The results of the IPMA analysis on both research samples still require improvement to improve port operational performance and port service user satisfaction.